2012
DOI: 10.2117/psysoc.2012.45
|View full text |Cite
|
Sign up to set email alerts
|

Influences of Optimism and Positive Orientation on Students’ Subjective Well-Being

Abstract: This study examined the influences of optimism and positive orientation on students' subjective well-being. Japanese university students (N = 325) completed a questionnaire. A factor analysis was conducted, and results showed that positive orientation can be divided into five categories-upward orientation, maintenance of undisturbed states, maintenance of status quo, downward comparison (positive), and downward comparison (negative)-depending on where one places the point of reference recognized as positive. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 22 publications
(39 reference statements)
0
4
0
Order By: Relevance
“…Self-esteem was positively correlated with all 6 dimensions of the PWBS in a Japanese sample (Pearson's r ranging from .433 to .714, Sasaki et al, 2020), therefore, we hypothesized that it would serve as a predictor of PWB here as well. Optimism has been shown to be related to life satisfaction among North American (Chang & Sanna, 2001) and Japanese individuals (Hashimoto & Koyasu, 2012). Because it has also been shown to predict life satisfaction, even in the presence of other variables (Lucas et al, 1996), we hypothesized that it would be able to predict SWB in the current sample as well.…”
Section: Introductionmentioning
confidence: 90%
“…Self-esteem was positively correlated with all 6 dimensions of the PWBS in a Japanese sample (Pearson's r ranging from .433 to .714, Sasaki et al, 2020), therefore, we hypothesized that it would serve as a predictor of PWB here as well. Optimism has been shown to be related to life satisfaction among North American (Chang & Sanna, 2001) and Japanese individuals (Hashimoto & Koyasu, 2012). Because it has also been shown to predict life satisfaction, even in the presence of other variables (Lucas et al, 1996), we hypothesized that it would be able to predict SWB in the current sample as well.…”
Section: Introductionmentioning
confidence: 90%
“… 31 Here, emotions are known to exert significant influences on well-being. 32 In other words, positive (as opposed to negative) emotions enhance one’s sense of well-being. Many argue that this concept is suitable for measuring short-term well-being (e.g., over a few months).…”
Section: Methodsmentioning
confidence: 99%
“…In another study, Hashimito and Koyasu (2012) conducted an empirical study to explore the effect of PO on Japanese university students' well-being. The results of SEM revealed that the two constructs are highly related to each other.…”
Section: Positive Orientationmentioning
confidence: 99%